Calculating the Sputtering Yield of Lithium, Sodium and Krypton Bombarded by Same Target Ion Using TRIM Simulation Program - Jawad, Enas Ahmed; Jassim, Mustafa Kamel; Tawfeek, Huda Majeed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Calculations of sputtering yield for Lithium,Sodium and Krypton bombarded by the same own ions are achieved by using TRIM program.The relation of angular dependent of sputtering yield for each ion/target is studied. Also, the dependence of the sputtering yield of target on the energy of the same ion is discussed and plotted graphically. Many researchers applied polynomials function to fit the sputtering data from experimental and simulation programs, however, we suggest to use Ior function for fitting the angular distribution of the sputtering yield. A New data for fitting coefficients of the used ion/target are presented by applying used function for the dependence of the sputtering yield on the ion energy.